The effect of wearing a synthetic rubber suit on hydrostatic lift and lung volume - Cortesi, M.; Zamparo, P.; Tam, E.; da Boit, M.; Gatta, G. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: In the Swimming World Championships 2009 swimmers utilized suits produced entirely, or partially, with industrial polymers. The effect of technical suits in determining the increase in swimming speed is still not fully understood, their advantage could be related to an increase of buoyancy (Benjanuvatra, 2002). The aim of this work was to evaluate the differences in hydrostatic lift and lung volume in swimmers wearing (or not wearing) a suit made of polyurethane/ neoprene. METHODS: In the first test, the hydrostatic lift 6.96 kg) were measured 0.03 m; 75.45± of 9 male swimmers (age 23.25±3.01; 1.80± while wearing a "standard" swim suit (S) or a full body technical suit (X-glide Arena Italy= Xg). After a maximal inspiration, the subjects were kept in position for 10 s under the water surface throughout a cable connected to a pulley system positioned on the swimming pool floor. The cable was also connected to a load cell (Globus, Italy) positioned on the pool's edge that allowed to measure the subject`s hydrostatic lift (the force with which their body tended to rise towards the water surface). In the second test, chest circumferences (maximal inspiration and maximal expiration) and lung volumes (VC: Vital Capacity, ERV: Expiratory Reserve Volume, VT: Tidal Volume, IRV: Inspiratory Reserve Volume) were measured in both conditions of suit. RESULTS: 3.99 N for S and 14.33± 4.53 The average values of hydrostatic lift were 14.51± N for Xg (R=0,94, P<0.05), for the chest circumferences during max. expiration (R=0,86) and max. inspiration (R=0,99) were 88,6±3,70 / 97,3±3,26 cm for S and 86,6±3,39 / 95,6±2,48 cm for Xg. The average values of lung volumes were: VC 6,31/6,14 L (<0,01), ERV 2,12/1,79 L (<0,01), VT 0,94/0,88 L, IRV 3,26/3,47 L (<0,05), respectively for S and XG. DISCUSSION: Hydrostatic lift was found to be smaller in Xg. A strong thoracic or abdominal compression caused by the technical suits could be tentatively related to the observed reduction in the chest circumferences during maximal inspiration and expiration as well as to the reduction in the lung volumes and in the hydrostatic lift. The improvement in performance obtained by wearing Xg is not related with a better static buoyancy. REFERENCES: Benjanuvatra N., Dawson G., Blanksby B.A., Elliott B.C., (2002) Comparison of buoyancy, passive and net active drag forces between Fastskin and standard swimsuits. Journal of Science and Medicine in Sport, 5(2), 115-23.